Determination of bifonazole and identification of its photocatalytic degradation products using UPLC‐MS/MS - Kryczyk, Agata; Żmudzki, Paweł; Hubicka, Urszula (Biomedical chromatography, 2017)
The main goal of the presented work was to investigate the effect of ZnO or/and TiO2 on the stability of bifonazole in solutions under UVA irradiation. To this end, a simple and reproducible UPLC method for the determination of bifonazole in the presence of its photocatalytic degradation products was developed. Linearity was studied in the range of 0.0046–0.15 mg mL−1 with a determination coefficient of 0.9996. Bifonazole underwent a photocatalytic degradation process under the experimental conditions used. Comparative studies showed that combination of TiO2/ZnO (1:1 w/w) was a more effective catalyst than TiO2 or ZnO with a degradation rate of up to 67.57% after 24 h of irradiation. Further, kinetic analyses indicated that the photocatalytic degradation of bifonazole in the mixture of TiO2/ZnO can be described by a pseudo‐first order reaction. Statistical comparison clearly indicated that the presence of TiO2/ZnO also affected the stability of bifonazole from a cream preparation after 15 h of UVA exposure (p < 0.05). Ten photodegradation products of bifonazole were identified for the first time and their plausible fragmentation pathways, derived from MS/MS data, were proposed. The main pathway in the photocatalytic transformation of bifonazole in the presence of ZnO or/and TiO2 involves hydroxylation of the methanetriyl group and/or adjacent phenyl rings and cleavage of the imidazole moiety.